2012
DOI: 10.1099/mic.0.054999-0
|View full text |Cite
|
Sign up to set email alerts
|

Lethality and cooperation of Pseudomonas aeruginosa quorum-sensing mutants in Drosophila melanogaster infection models

Abstract: The virulence profiles of Pseudomonas aeruginosa quorum-sensing (QS) mutants were assessed in Drosophila melanogaster feeding and nicking infection models. Functional RhlIR and LasIR QS systems were required for killing in the fly feeding infection model but were not essential in the fly nicking infection model. Mixed infections between PAO1 and strains harbouring mutations in lasR, rhlI and lasI rhlI resulted in increased lethality in the fly feeding model compared with either isolate alone. These results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…In the nicking model rapid killing within 1–2 days after pricking flies with a needle dipped into a bacterial culture is observed, whereas the feeding model allows to monitor an extended infection process of 1–2 weeks after ingestion of a high concentration of bacteria by the flies. Using these models, considerable strain variation in virulence of P. aeruginosa to Drosophila was observed (Lutter et al, 2012) coinciding with similar observations for P. fluorescens group bacteria (Olcott et al, 2010). The variations in the pathogenicity are likely to mirror differences in the genomic equipage with relevant virulence genes and in the regulation of these genes in the different strains.…”
Section: Molecular Basis Of Insect Interaction In Prominent Pathogenisupporting
confidence: 75%
“…In the nicking model rapid killing within 1–2 days after pricking flies with a needle dipped into a bacterial culture is observed, whereas the feeding model allows to monitor an extended infection process of 1–2 weeks after ingestion of a high concentration of bacteria by the flies. Using these models, considerable strain variation in virulence of P. aeruginosa to Drosophila was observed (Lutter et al, 2012) coinciding with similar observations for P. fluorescens group bacteria (Olcott et al, 2010). The variations in the pathogenicity are likely to mirror differences in the genomic equipage with relevant virulence genes and in the regulation of these genes in the different strains.…”
Section: Molecular Basis Of Insect Interaction In Prominent Pathogenisupporting
confidence: 75%
“…aeruginosa to establish acute infections (3136). We also found that in ASM in the absence of pig lung, lasR mutants were less fit than the WT.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the well-characterized PAO1 wild-type (WT) strain and two lasR mutant strains which do not respond to the QS signal N -(3-oxododecanoyl)- l -homoserine lactone (3-oxo-C 12 -HSL) (49). QS controls the expression of various exoproducts (49) and facilitates the establishment of acute infection (3136). However, mutants that have lost LasR function and so do not respond to 3-oxo-C 12 -HSL commonly arise in chronic CF infections (9, 10, 12) and ventilator-associated pneumonia (50).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, various commensal flora in different laboratories may also impact the severity of the outcome of the infection (see also below). Screens of P. aeruginosa mutants, in either injured or orally infected flies, have highlighted the involvement of twitching motility factors Potvin et al, 2003), QS regulators , and a number of either previously known or newly discovered QS regulated genes, in full virulence towards Drosophila (Chugani et al, 2001;Lau et al, 2003;Erickson et al, 2004;Kim et al, 2008;Lutter et al, 2012). Moreover, we showed the importance of T3SS for full virulence of the cystic fibrosis isolate CHA and identified new regulators of QS or T3SS, which are commonly required for full virulence of PAO1 in amoebae, mice and orally infected flies (Fauvarque et al, 2002;Alibaud et al, 2008).…”
Section: P Aeruginosa-induced Fly Pathogenesismentioning
confidence: 99%